Twelve New Genomic Loci Associated With Bone Mineral Density - Liu, Lu; Zhao, Min; Xie, Zong-Gang; Liu, Ju; Peng, Hui-Ping; Pei, Yu-Fang; Sun, Hong-Peng; Zhang, Lei (Frontiers in Endocrinology, 2020)
Aiming to identify more genomic loci associated with bone mineral density (BMD), we conducted a joint association analysis of 2 genome-wide association study (GWAS) by the integrative association method multi-trait analysis of GWAS (MTAG). The first one is the single GWAS of estimated heel BMD (eBMD) in the full UK biobank (UKB) cohort (N=426,824), and the second one is the GWAS meta-analysis of total body BMD (TB-BMD) in 66,628 participants from 30 studies. Approximate conditional association analysis was performed in the identified novel loci to identify secondary association signal. Statistical fine-mapping was conducted to prioritize plausible credible risk variants (CRVs). Candidate genes were prioritized based on the analyses of cis- expression quantitative trait locus (cis-eQTL) and cis-protein QTL (cis-pQTL) information as well as the functional category of the SNP. By integrating the information carried in over 490,000 participants, this largest joint analysis of BMD GWAS identified 12 novel genomic loci at the genome-wide significance level (GWS, p=5.0×10-8), 9 of which were for eBMD and 4 were for TB-BMD, explaining an additional 0.11% and 0.23% heritability for the two traits, respectively. These loci include 1p33 (lead SNP rs10493130, peBMD=3.19×10-8), 5q13.2 (rs4703589, peBMD=4.78×10-8), 5q31.3 (rs9324887, pTB-BMD=1.36×10-9), 6p21.32 (rs6905837, peBMD=3.32×10-8), 6q14.1 (rs10806234, peBMD=2.63×10-8), 7q21.11 (rs10806234, pTB-BMD=3.37×10-8), 8q24.12 (rs11995866, peBMD=6.72×10-9), 12p13.31 (rs1639122, peBMD=4.43×10-8), 12p12.1 (rs58489179, peBMD=4.74×10-8), 12q24.23 (rs75499226, peBMD=1.44×10-8), 19q13.31 (rs7255083, pTB-BMD=2.18×10-8) and 22q11.23 (rs13056137, pTB-BMD=2.54×10-8). All lead SNPs in these 12 loci are nominally significant in both original studies as well as consistent in effect direction between them, providing solid evidence of replication. Approximate conditional analysis identified one secondary signal in 5q13.2 (rs11738874, pconditional=5.06×10-9). Statistical fine-mapping analysis prioritized 269 CRVs. A total of 65 candidate genes were prioritized, including those with known biological function to bone development (such as FGF1, COL11A2 and DEPTOR). Our findings provide novel insights into a better understanding of the genetic mechanism underlying bone development as well as candidate genes for future functional investigation.